The emerging of rich internet applications in web applications: their usability towards good user experience - Nooralisa Mohd Tuah; Dg. Senandong Ajor (2010)
The internet technology has been evolved from static web information to dynamic web presentation and now come to the rich internet application environment. The evolvement come through due to pursue the massive web technologies in Rich Internet Application (RIA). The main emphasis of this project is to evaluate the application usability concerning of two feedback types. One of these would be an e-commerce application system with RIA implementation and the other would be a standard e-commerce application. In order to determine the direction of this experiment, an empirical study was conducted with 62 participants where all of them were undergraduate students. This study was implementing a within users design as a method for this experiment. An e-commerce application system was developed as a model to obtain the evaluation result. Statistical analysis was then applied to present the significant outcome. There was a statistically significant difference for this preference where it is clearly showed that in this context of study, an e-commerce application system with the presence of RIA element gives a significant result and thus, user preferred the RIA implementation for this e-commerce web application.